Litter Decomposition and Diversity of Soil Macrofauna on Industrial Plantation Forest of Nyawai - Pranatasari Dyah Susanti; Wawan Halwany (Jurnal Ilmu Kehutanan)
The use of fast-growing tree species is necessary to meet the demand of timber. However, the information with regard the fertility of the soil for planting of these species is still limited. This study aimed to obtain data and information on the litter production and its rate of decomposition as well as soil macrofauna diversity on Industrial Plantation Forest of nyawai (Ficus variegate. Blume) with three different age classes. This study used a quantitative method. Sample plots were determined purposively with consideration of the representation of age. The observed variables included the amount of production of litter, decomposition rate of litter, and soil macrofauna using two methods, i.e. monolith or soil sampling (PCT) for soil macrofauna underground the soil and trap wells (PSM) for macrofauna on soil surface. The results showed in the 6-year-old stands showed the best litter ecomposition rates, since 48.31% of litter was decomposed at a rate of 11%. At this age class, diversity of macrofauna also has the highest score as 1.08, although that value was still in the low category.